2012
DOI: 10.1371/journal.pntd.0001711
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PGL-I Seropositivity on the Protective Effect of BCG Vaccination among Leprosy Contacts: A Cohort Study

Abstract: Background Contacts of leprosy patients are at increased risk of developing leprosy and need to be targeted for early diagnosis. Seropositivity to the phenolic glycolipid I (PGL-I) antigen of Mycobacterium leprae has been used to identify contacts who have an increased risk of developing leprosy. In the present study, we studied the effect of seropositivity in patient contacts, on the risk of developing leprosy, stratified by Bacille Calmette Guerin (BCG) vaccination aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 18 publications
4
54
1
11
Order By: Relevance
“…A previous study in Rio de Janeiro involving 2,135 HC revealed seropositivity rate of 16% (19) , while a study in hyperendemic municipalities in the Brazilian Amazon Region involving 1,592 school children revealed a seropositivity of 48.8%, and of 256 HC, 41.8% were seropositive for APGL-I (20) . In the endemic areas of Brazil, the expected APGL-I seropositivity rate is 7% among non-contacts and 10% among HC (14) .…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…A previous study in Rio de Janeiro involving 2,135 HC revealed seropositivity rate of 16% (19) , while a study in hyperendemic municipalities in the Brazilian Amazon Region involving 1,592 school children revealed a seropositivity of 48.8%, and of 256 HC, 41.8% were seropositive for APGL-I (20) . In the endemic areas of Brazil, the expected APGL-I seropositivity rate is 7% among non-contacts and 10% among HC (14) .…”
Section: Discussionmentioning
confidence: 81%
“…Most MB cases were diagnosed in unvaccinated APGL-I positive HC. Vaccination increased the rate of developing clinical manifestations of PB in APGL-I-positive HC (19) . BCG vaccination increases tumor necrosis factor alpha (TNF-α) production in MB patients, and interferon gamma (IFN-γ and interleukin-17 (IL-17) production in PB patients (22) .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations